Bacterial Biofilms and Increased Bacterial Counts Are Associated with Airway Stenosis. (10th February 2014) - Mazhar, Kashif; Gunawardana, Manjula; Webster, Paul; Hochstim, Christian; Koempel, Jeffery; Kokot, Niels; Sinha, Uttam; Rice, Dale; Baum, Marc
Abstract : Objectives: Most airway stenoses are acquired secondary to the use of prolonged endotracheal intubation. Antibiotics have been shown to decrease local inflammation and granulation tissue formation in the trachea. However, antibiotic therapy is not 100% effective in preventing or treating granulation tissue formation. Development of bacterial biofilms may explain this finding. This study evaluates the difference between tracheal stenotic segments and normal trachea in terms of (1) presence of bacterial biofilms, (2) quantitative bacterial counts, and (3) inflammatory markers. Study Design: Cross‐sectional study. Setting: Tertiary care academic medical center. Subjects: A total of 12 patients were included in the study. Tissue from stenotic segments from 6 patients with airway stenosis undergoing open airway procedures were compared with tracheal tissue from 6 patients without airway stenosis undergoing tracheostomy. Methods: Scanning electron microscopy for biofilm detection, quantitative polymerase chain reaction for quantitative analysis of bacterial count, and immunohistochemistry were performed for inflammatory markers transforming growth factor β1 (TGF‐β1) and SMAD3. Results: Compared with the patients without airway stenosis, patients in the airway stenosis group showed presence of bacterial biofilms, a significantly higher expression of 16S rRNA gene copies per microgram of tissue (187.5 vs 7.33, P =. 01), and higher expression of TGF‐β1 (91% vs 8%, P <. 001) and SMAD3 (83.5% vs 17.8%, P <. 001). Conclusion: Bacterial biofilms, increased bacterial counts, and higher expression of TGF‐β1 and SMAD3 are associated with airway stenosis.